DEVELOPING SOCIAL RESPONSIBILITY IN MIILTARY OFFFICERS: STATEMENT OF ISSUE - Lyudmila A. Saenko; Shamsuddin Sh. Piroglanov (Вестник Северо-Кавказского федерального университета)
The article dwells on the issue of shaping social responsibility in the military. The authors conduct an analysis of the term “social responsibility” from the viewpoint of the phenomenological approach. Special attention is paid to the factors facilitating developing social responsibility in military officers. There is also a focus on the conditions that will promote shaping social responsibility in military detachments. The authors conclude with offering their own definition for social responsibility.